High-thermal-conductivity, high-electric-conductivity and high-thermal-conductivity interface material and preparation method and application thereof
By oriented arrangement of carbon fibers and stacked graphene films in a silicone rubber matrix, a hierarchical thermal conduction path of "trunk-branch-interface reinforcement" is constructed, which solves the problem of insufficient thermal conductivity of traditional thermal interface materials in high-power scenarios and achieves efficient heat transfer and material performance improvement.
Patent Information
- Application Number
- CN202511190280.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-28
AI Technical Summary
Existing thermal interface materials have insufficient thermal conductivity in high-power scenarios. The thermal conduction path of traditional carbon fiber thermal pads is discontinuous, and during the heat transfer process, poor contact between fibers can easily lead to thermal resistance accumulation and phonon scattering loss. The preparation process of graphene film thermal pads is still unclear.
The carbon fiber is oriented in the silicone rubber matrix by a scraper coating process. Combined with the lamination technology, the graphene film penetrates the gasket in the vertical direction to form a hierarchical heat conduction path of "main trunk-branch-interface reinforcement". The graphene film serves as the main channel, the carbon fiber serves as the branch network, and the ceramic micro powder bridges the interface area to construct a variety of heat flow paths.
It achieves a synergistic improvement in thermal conductivity and mechanical properties, minimizes directional deflection and scattering losses during heat transfer, improves heat transfer efficiency, and is suitable for industrial applications.
Smart Images

Figure CN121019042A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of thermal interface materials of electronic equipment, and particularly relates to a high-thermal-conductivity and high-electric-conductivity thermal interface material and a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of 5G communication, artificial intelligence chips and new energy automobile power modules, the integration and power density of electronic devices present exponential growth. The heat dissipation problem has become a key bottleneck restricting performance improvement. As a functional material filling the micro gap between the heat source and the heat sink, the thermal conductivity of the thermal interface material directly affects the heat dissipation efficiency. Traditional ceramic thermal interface materials (such as Al2O3, ZnO, etc.) have low thermal conductivity (usually <10 Wm -1 K-1), which is difficult to meet the heat dissipation requirements of new-generation high-power chips. Therefore, developing a new type of thermal interface material with high thermal conductivity has become an important research direction to solve the heat dissipation problem of electronic equipment.
[0003] Carbon fibers have become an ideal reinforcing phase for preparing high-performance thermal pads due to their high axial thermal conductivity, low density and excellent mechanical properties. However, the thermal conductivity of traditional carbon fiber thermal pads still faces major challenges. Although the orientation technology has been developed, the orientation arrangement of carbon fibers in the silicone rubber matrix has been significantly improved. However, the thermal conduction network composed of multiple carbon fibers connected end to end by single short carbon fiber powder has a discontinuous thermal conduction path, introduces a large number of interfaces, and heat is easily lost due to poor contact between fibers during transmission, resulting in thermal resistance accumulation and aggravation of phonon scattering loss, so that the actual thermal conductivity is much lower than the theoretical value. In high-power scenarios, the thermal conductivity limit of the single carbon fiber system is still difficult to meet the requirements.
[0004] Graphene film (GF) as a new type of high-thermal-conductivity material has a thermal conductivity of about 1000 Wm -1 K-1, and excellent flexibility and directional thermal conduction characteristics, providing a new idea for breaking through the thermal conduction bottleneck of carbon fiber pads. However, the research on graphene film thermal pads is still in its infancy, and the process for preparing graphene film thermal pads with high thermal conductivity is not clear. SUMMARY
[0005] In view of the deficiencies in the prior art, the application provides a high-thermal-conductivity and high-electric-conductivity thermal interface material and a preparation method and application thereof. The directional arrangement of carbon fibers in the silicone rubber matrix is realized by means of a doctor blade coating process, and the graphene film is ensured to penetrate the pad along the vertical direction by means of a layering technology, so as to form a "trunk-branch-interface reinforcement" hierarchical thermal conduction path. The "thermal conduction island" problem of traditional composite materials is solved through the synergistic effect of the multi-scale path, and the thermal conductivity and mechanical properties of the material are synergistically improved.
[0006] The technical scheme of the application is as follows:
[0007] This invention provides a high thermal conductivity and electrical conductivity interface material, which comprises alternating layers of graphene film and carbon fiber / silicone composite layer.
[0008] In the high thermal conductivity and electrical-thermal interface material, carbon fibers are oriented in a direction perpendicular to the surface of the graphene film, and the carbon fibers are in direct contact with the graphene film.
[0009] The raw materials for the carbon fiber / silicone composite layer include a silicone matrix, carbon fiber, and ceramic micro powder.
[0010] The graphene film, acting as the vertical "main channel," undertakes the core heat conduction function, while the oriented carbon fibers, forming a "branch network," not only share some of the heat transfer work but also channel heat to the graphene film's main structure. Furthermore, ceramic particles form bridging structures at the interface to reduce interfacial thermal resistance. This structural design minimizes directional deflection and scattering losses during heat transfer.
[0011] As a specific embodiment of the present invention, the spherical ceramic micro powder is at least one of alumina, zinc oxide, boron nitride, aluminum nitride, and silicon carbide. Preferably, the ceramic micro powder is spherical, and more preferably, the particle size of the ceramic micro powder is 1-5 μm.
[0012] As a specific embodiment of the present invention, the silicone matrix comprises the following raw materials in parts by weight: 100 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 1-3 parts of platinum catalyst, and 0.1-0.3 parts of acetylenecyclohexanol.
[0013] In a specific embodiment of the present invention, the amount of carbon fiber added is 50-150% of the weight of the silica matrix, and the amount of ceramic micro powder added is 50-150% of the weight of the silica matrix.
[0014] As a specific embodiment of the present invention, the graphene film, carbon fiber, and ceramic micro powder need to undergo surface modification treatment.
[0015] As a specific embodiment of the present invention, the amount of the modifier is 0.2-1.0% of the weight of the graphene film, carbon fiber, and ceramic micro powder, respectively; preferably, the surface modifier used in the surface modification treatment is a silane coupling agent.
[0016] As a specific embodiment of the present invention, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloyloxypropyl, vinyltriethoxysilane, vinyltrimethoxysilane, and hexadecyltrimethoxysilane.
[0017] Secondly, the present invention provides a method for preparing the above-mentioned high thermal conductivity and electrical conductivity interface material, wherein carbon fiber, ceramic micro powder and silicone matrix are mixed evenly and coated evenly on the surface of graphene film using a scraper; the mixture is alternately stacked and cured under pressure to prepare the high thermal conductivity and electrical conductivity interface material.
[0018] As a specific embodiment of the present invention, the following steps are included:
[0019] (1) Surface modification treatment of graphene film, carbon fiber and ceramic micro powder;
[0020] (2) Prepare the raw materials for the silicone matrix, stir, and obtain the silicone rubber matrix;
[0021] (3) Add the carbon fiber and ceramic micro powder modified in step (1) to the silicone rubber matrix in step (2), stir, and form a paste.
[0022] (4) Transfer the paste from step (3) to the surface of the graphene film and scrape it in one direction with a scraper so that the carbon fibers are oriented along the scraping direction;
[0023] (5) Place the graphene film with CF / SR sheets on the surface into the curing mold in sequence and stack them layer by layer; after curing, the product is obtained.
[0024] As a specific embodiment of the present invention, the stirring in step (1) or step (2) is carried out under vacuum conditions.
[0025] Thirdly, the application of the above-mentioned high thermal conductivity and electrical conductivity interface material or the high thermal conductivity and electrical conductivity interface material prepared by the above-mentioned preparation method in the field of heat dissipation of electronic devices is provided.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] 1. The graphene film running through both ends of the gasket forms a vertical "main heat conduction channel," which, thanks to its high intrinsic thermal conductivity, allows for rapid heat transfer along the graphene film. Because the graphene film maintains a strictly vertical orientation within the gasket, heat flow does not require directional deflection during transfer, minimizing phonon scattering losses caused by path bends and achieving a significant improvement in thermal conductivity.
[0028] 2. After the coating and orientation process, the carbon fibers are vertically oriented within the silicone rubber matrix, forming dense "branched thermally conductive channels." These carbon fibers not only construct continuous thermally conductive paths within the CF / SR sheets, transforming the originally non-thermally conductive silicone rubber matrix into a functional region with significant thermal conductivity, but also achieve efficient heat transfer from the branched network to the main channels through direct contact with adjacent graphene films.
[0029] 3. Some carbon fibers form a "bridging structure" with the graphene film through physical contact, while Al2O3 particles exhibit multiple distribution patterns in the interface region. They exist both at the contact points between the carbon fibers and the graphene film and fill the gaps between the carbon fibers. This composite interface structure constructs diverse heat flow paths: direct contact paths between carbon fibers, indirect bridging paths between carbon fibers, Al2O3 particles, and continuous conduction paths between Al2O3 particles. The synergistic effect of these paths significantly improves the heat transfer efficiency from the SR matrix to the carbon fiber network and then to the main channels of the graphene film, effectively solving the heat accumulation problem caused by "thermal islands" in traditional composite materials.
[0030] 4. Mass production can be achieved through doctor blade coating orientation and layered curing. The process is simple and fast, and the structure can be arbitrarily adjusted, making it suitable for industrial applications. Attached Figure Description
[0031] Figure 1 This is a process diagram illustrating the preparation of the high thermal conductivity graphene-based thermal interface material of the present invention;
[0032] Figure 2 The images shown are SEM images of the thermally conductive materials prepared in Examples 1-3 of this invention. Detailed Implementation
[0033] Example 1: Preparation of GF@CF-40
[0034] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add carbon fiber (10 μm in diameter and 200 μm in length), alumina particles (2 μm and 10 μm mixed in a 3:7 ratio), and graphene film, soak for 3 h, and dry at 120 °C.
[0035] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0036] (3) Preparation of CF / SR paste: Add 5.0g of modified carbon fiber and 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0037] (4) Coating orientation: The paste is coated onto the surface of a 20μm thick graphene film, and the height of the scraper is adjusted to 40μm so that the thickness of the CF / SR sheet is 40μm.
[0038] (5) Curing: Cut the CF / SR coated sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF@CF-40 gaskets.
[0039] Example 2: Preparation of GF@CF-60
[0040] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add carbon fiber (10 μm in diameter and 200 μm in length), alumina particles (2 μm and 10 μm mixed in a 3:7 ratio), and graphene film, soak for 3 h, and dry at 120 °C.
[0041] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0042] (3) Preparation of CF / SR paste: Add 5.0g of modified carbon fiber and 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0043] (4) Coating orientation: The paste is coated onto the surface of a 20μm thick graphene film, and the height of the scraper is adjusted to 60μm so that the thickness of the CF / SR sheet is 60μm.
[0044] (5) Curing: Cut the CF / SR coated sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF@CF-60 gaskets.
[0045] Example 3: Preparation of GF@CF-20
[0046] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add carbon fiber (10 μm in diameter and 200 μm in length), alumina particles (2 μm and 10 μm mixed in a 3:7 ratio), and graphene film, soak for 3 h, and dry at 120 °C.
[0047] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0048] (3) Preparation of CF / SR paste: Add 5.0g of modified carbon fiber and 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0049] (4) Coating orientation: The paste is coated onto the surface of a 20μm thick graphene film, and the height of the scraper is adjusted to 20μm so that the thickness of the CF / SR sheet is 20μm.
[0050] (5) Curing: Cut the CF / SR coated sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF@CF-20 gaskets.
[0051] Comparative Example 1: Graphene-free film (pure CF / SR gasket)
[0052] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add carbon fiber (10 μm in diameter and 200 μm in length) and alumina particles (2 μm and 10 μm mixed in a 3:7 ratio), soak for 3 h, and dry at 120 °C.
[0053] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0054] (3) Preparation of CF / SR paste: Add 5.0g of modified carbon fiber and 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0055] (4) Coating orientation: Coat the paste onto the surface of the release film, and adjust the height of the squeegee to 40μm so that the CF / SR sheet thickness is 40μm;
[0056] (5) Curing: Cut the CF / SR sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF@CF-20 gaskets.
[0057] Comparative Example 2: No carbon fiber (pure GF / SR gasket)
[0058] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add alumina particles (2μm and 10μm mixed in a 3:7 ratio) and graphene film, soak for 3h, and dry at 120℃.
[0059] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0060] (3) Preparation of CF / SR paste: Add 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0061] (4) Random orientation: The paste was randomly spread on the surface of a 20μm thick graphene film, and the thickness of the SR sheet was controlled to be 40μm;
[0062] (5) Curing: Cut the SR coated sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF / SR gaskets.
[0063] Comparative Example 3: Non-directional arrangement of carbon fibers
[0064] (1) Surface modification: Prepare an ethanol solution of 0.5% γ-aminopropyltriethoxysilane, add carbon fiber (10 μm in diameter and 200 μm in length), alumina particles (2 μm and 10 μm mixed in a 3:7 ratio), and graphene film, soak for 3 h, and dry at 120 °C.
[0065] (2) Preparation of silicone matrix: Take 10.0g vinyl silicone oil, 0.9g hydrogen-containing silicone oil and 0.02g acetylene cyclohexanol, stir under vacuum for 15min, add 0.15g platinum catalyst, and continue stirring for 5min to obtain SR matrix;
[0066] (3) Preparation of CF / SR paste: Add 5.0g of modified carbon fiber and 5.0g of modified alumina to 5.0g of SR matrix, stir until homogeneous, and degas under vacuum;
[0067] (4) Random orientation: The paste was randomly spread on the surface of a 20μm thick graphene film, and the thickness of the CF / SR sheet was controlled to be 40μm;
[0068] (5) Curing: Cut the CF / SR coated sheets according to the mold size, place them into the mold one by one and stack them layer by layer. Curing at 100℃ and 2MPa for 2h yields GF@CF-20 gaskets.
[0069] The thermally conductive materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the results are shown in Table 1.
[0070] Table 1: Test results of the thermally conductive materials prepared in Examples 1-3 and Comparative Examples 1-3
[0071] Item Thermal conductivity / Wm -1 K-1]]> Example 1 116.7 Example 2 86.3 Example 3 176.5 Comparative Example 1 20 Comparative Example 2 45.2 Comparative Example 3 71.6
[0072] The above description is merely a basic explanation of the concept of this invention, and any equivalent modifications made based on the technical solution of this invention shall fall within the protection scope of this invention.
Claims
1. A high thermal conductivity and electrical-thermal interface material, characterized in that, The high thermal conductivity and electrical-thermal interface material includes alternating layers of graphene film and carbon fiber / silicone composite layer. In the high thermal conductivity and electrical-thermal interface material, carbon fibers are oriented in a direction parallel to the surface of the graphene film, and the carbon fibers are in direct contact with the graphene film. The raw materials for the carbon fiber / silicone composite layer include a silicone matrix, carbon fiber, and ceramic micro powder.
2. The high thermal conductivity and electrical-thermal interface material according to claim 1, characterized in that, The spherical ceramic micro powder is at least one of alumina, zinc oxide, boron nitride, aluminum nitride, and silicon carbide. Preferably, the ceramic micro powder is spherical, and more preferably, the particle size of the ceramic micro powder is 1-5 μm. And / or, the silicone matrix comprises the following raw materials in parts by weight: 100 parts vinyl silicone oil, 5-10 parts hydrogen-containing silicone oil, 1-3 parts platinum catalyst, and 0.1-0.3 parts acetylenecyclohexanol.
3. The high thermal conductivity and electrical-thermal interface material according to claim 1 or 2, characterized in that, The amount of carbon fiber added is 50-150% of the weight of the silica matrix, and the amount of ceramic micro powder added is 50-150% of the weight of the silica matrix.
4. The high thermal conductivity and electrical-thermal interface material according to any one of claims 1-3, characterized in that, The graphene film, carbon fiber, and ceramic micro powder need to undergo surface modification treatment.
5. The high thermal conductivity and electrical-thermal interface material according to claim 4, characterized in that, The amount of the modifier used is 0.2-1.0% of the weight of the graphene film, carbon fiber, and ceramic micro powder, respectively; preferably, the surface modifier used in the surface modification treatment is a silane coupling agent.
6. The high thermal conductivity and electrical-thermal interface material according to claim 4 or 5, characterized in that, The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyl, vinyltriethoxysilane, vinyltrimethoxysilane, and hexadecyltrimethoxysilane.
7. A method for preparing a high thermal conductivity and electrical-thermal interface material according to any one of claims 1-6, characterized in that, Carbon fiber, ceramic micro powder and silicone matrix are mixed evenly and then uniformly coated onto the surface of graphene film using a scraper; the mixture is then stacked alternately and cured under pressure to prepare a high thermal conductivity and electrical-thermal interface material.
8. The preparation method according to claim 7, characterized in that, Specifically, the following steps are included: (1) Surface modification treatment of graphene film, carbon fiber and ceramic micro powder; (2) Prepare the raw materials for the silicone matrix, stir, and obtain the silicone rubber matrix; (3) Add the carbon fiber and ceramic micro powder modified in step (1) to the silicone rubber matrix in step (2), stir, and form a paste. (4) Transfer the paste from step (3) to the surface of the graphene film and scrape it in one direction with a scraper so that the carbon fibers are oriented along the scraping direction; (5) Place the graphene film with CF / SR sheets on the surface into the curing mold in sequence and stack them layer by layer; after curing, the product is obtained.
9. The preparation method according to claim 7, characterized in that, The stirring in step (1) or step (2) is carried out under vacuum conditions.
10. The application of the high thermal conductivity and electrical conductivity interface material according to any one of claims 1-6 or the high thermal conductivity and electrical conductivity interface material prepared by the preparation method according to any one of claims 7-9 in the field of heat dissipation of electronic devices.
Citation Information
Cited By
High-thermal-conductivity composite gasket as well as preparation method and application thereof
CN122125959A